Design estratégico no ambientes dos FAB LABS Acadêmicos: inovação de significado para impulsionar a inovação social - Chaves, Carolina Wiedemann (Universidade do Vale do Rio dos Sinos, 2024)
Digital technologies have rapidly integrated into everyday life, also impacting the production of artifacts through electronic systems. Digital fabrication, which employs computational means for design and computer-controlled machinery for production, has played a central role in this process. In this context, Fab Labs have emerged as spaces that, aligned with the Maker Culture, provide the general public with access to digital fabrication machinery. Many of these laboratories are linked to educational institutions and are classified as Academic Fab Labs. Despite the potential of Fab Labs to promote the inclusion of society in digital fabrication, their ability to impact society beyond the academic community has yet to be fully explored. Considering that higher education institutions are guided by the principle of the inseparability of Teaching, Research, and Extension, Academic Fab Labs, by offering access to Maker Culture and digital fabrication, present significant potential to promote this integration. In this regard, Strategic Design, linked to Social Innovation and Innovation of Meaning, emerges as a promising approach to explore this potential. This research aims to propose a Design Strategy to reframe Academic Fab Labs, using Design-Driven Innovation as a key tool. The methodology adopted is qualitative, based on the problematizing approach of Strategic Design, focusing on the movements of Listening, Interpreting, and Disseminating, which are characteristic of Design-Driven Innovation. In the “Listening” phase, interactions with various interpreters were carried out to gather existing knowledge on the topic. Additionally, two Academic Fab Labs, one linked to a public institution and another to a private institution, both located in Porto Alegre (RS), were selected as the study field. Key interpreters were interviewed, future scenario workshops were conducted, and unsystematic observations were made. In the “Interpreting” phase, a project concept was developed based on the signals captured during the listening phase. This process resulted in the formulation of a Strategic Design Proposal for Academic Fab Labs, which includes a self-assessment tool for Fab Labs to analyze their configuration and performance concerning the inseparability of Teaching, Research, and Extension, as well as Social Innovation practices. The key concepts of this proposal are purpose, sharing, and networking. Finally, in the “Disseminating” phase, a prototype of the proposal was presented to the Fab Labs involved in the study. The self-assessment tool aims to foster Fab Labs' self-awareness, enabling them to pursue their reframing according to the contexts in which they operate and the dynamics of organizational culture. The (Re)Framing Journey of Academic Fab Labs is composed of three tools: an introductory questionnaire (“How I perceive myself”), a deep reflection on the space (“Looking in the Mirror”), and a future planning panel (“(Re)Framing and Future”). The research suggests future studies to develop dynamic platforms to disseminate and enhance the (Re)Framing journey, as well as to explore its adaptation to non-academic Fab Labs and its application in other laboratories around the world.
Keywords: Design estratégico; Fab Lab Acadêmico; Inovação social; Design-driven innovation; Inovação de significado; Strategic design; Academic Fab Lab; Social innovation; Innovation of meaning; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial